The Influence of Digestate and Mineral Fertilisers on Yields and Content of Nitrates and Ascorbic Acid in Kohlrabi Bulbs - Tomáš Lošák; Tereza Zlámalová; Monika Vítězová; Jaroslav Hlušek; Petr Škarpa; Jiří Fryč; Tomáš Vítěz; Jan Mareček (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2014)
In a one-year vegetation pot experiment we compared the effect of the digestate from a biogas plant and mineral fertilisers on yield and quality parameters of kohlrabi, variety Moravia. Four treatments were used in the trial: 1) untreated control, 2) urea, 3) digestate, 4) urea, triple super phosphate, KCl, MgSO4. The rate of N was the same in treatments 2–4, i.e. 1.5 g N/pot. In treatment 4 the rate of P, K and Mg corresponded with the rate of these nutrients in the digestate treatment (3). The inhibited growth of kohlrabi after the application of NPKMg (4) was obviously the consequence of early planting after the application of fertilisers (5 days) and of the salinity of the small content of soil in the pot and resulted in the lowest weight of single bulbs (69 g), followed by the unfertilised control treatment (75 g). After the application of the digestate (treatment 3) the weight of single bulbs significantly increased (126 g) compared to the urea treatment (101 g) and all the other treatments. The content of ascorbic acid in the fertilised treatments did not differ (441–458 mg/kg) but it increased significantly compared to the unfertilised treatment (398 mg/kg). There were significant differences among all the fertilised treatments (1–2–3–4) in the bulb nitrate content (346–1,147–815–1,091 mg NO3−/kg fresh matter, respectively). After digestate application their content decreased significantly to 815 mg NO3−/kg fresh matter. Digestate treatment resulted in comparable or better yields and qualitative parameters compared to all the other treatments.